(untitled) (American Journal of Arts and Human Science, 2025)
This study explores the connection between the work environment and job performance of non-teaching employees in higher education institutions (HEIs) in Region 10. It focuses on employees such as Academic Secretaries, Librarians, Registrar Staff, and Student Affairs personnel, who play essential roles in institutional operations. Using a mixed-method approach, qualitative and quantitative data were collected from 300 respondents through surveys and interviews. Participants were selected using purposive sampling to ensure diverse experiences and key roles were represented. A structured questionnaire measured demographics, work environment perceptions, and job performance indicators, including productivity, people skills, and attendance. The study aimed to determine the levels of work environment satisfaction and job performance among non-teaching employees. It sought to describe the demographic and professional profiles of respondents, assess their perceptions of the work environment, and evaluate perceived job performance. It also examined significant differences in job performance based on demographic and professional characteristics and analyzed the relationship between work environment assessments and job performance. Descriptive statistics were used, including frequency, percentage, mean, and standard deviation. Pearson’s r, F-test, and T-test determined significant relationships and differences in job performance. Results showed that a positive work environment significantly improves job performance. Factors such as clear role expectations, fair compensation, leadership style, and professional growth opportunities were critical. Interviews emphasized the need for employee recognition and career development. The study concludes that improving workplace conditions benefits both employees and institutions. HEIs are recommended to implement the Work Enhancement Plan, including flexible work arrangements to reduce absenteeism.